2016
DOI: 10.3906/tar-1511-78
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and antioxidant characteristics of blackberry cultivars from East Anatolia

Abstract: Blackberry is commonly used both in the fresh and the processing market. In the present study antioxidant capacity, organic acids, phenolic compounds, vitamin C, and sugars content of blackberry cultivars grown in the east of Turkey were determined. Phenolic compounds, organic acids, vitamin C, and sugars were determined by HPLC. Antioxidant capacity was determined by spectrophotometric methods. The cultivar Cherokee had the highest antioxidant capacity (48.900 µmol TE g -1 ), and the cultivar Jumbo had the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
3
16
1
1
Order By: Relevance
“…Regarding the antioxidant capacity in both the watersoluble and the water-insoluble extract, there was a significant difference between the varieties but not between the harvest periods. Influence of variety on TAC was confirmed also for other species by various authors, f. e. by Gündoğdu et al [2016] studied blackberry, or by Barátová et al [2015] in case of basil with significant influence on TPC and TAC as well (estimated by DPPH method).…”
Section: Total Antioxidant Capacity By Dpph and Pcl Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Regarding the antioxidant capacity in both the watersoluble and the water-insoluble extract, there was a significant difference between the varieties but not between the harvest periods. Influence of variety on TAC was confirmed also for other species by various authors, f. e. by Gündoğdu et al [2016] studied blackberry, or by Barátová et al [2015] in case of basil with significant influence on TPC and TAC as well (estimated by DPPH method).…”
Section: Total Antioxidant Capacity By Dpph and Pcl Methodssupporting
confidence: 60%
“…Statistically significant differences among cultivars in terms of phenolic content (P < 0.05) in blackberry were found according to Gündoğdu et al [2016]. The cultivars showed different tendencies for antioxidative properties (antioxidative capacity, total polyphenols, phenolic compounds) of tested Hungarian and Persian walnut cultivars [Bujdosó et al 2016].…”
Section: Total Polyphenol Content (Tpc)mentioning
confidence: 95%
“…Additionally, strawberries, raspberries, cranberries, blackberries and pomegranates were reported also as very important sources of vitamin C. Hakkinen et al [26] found high content of this vitamin in strawberries (47.8 mg/100 g) and cranberries (20.0 mg/100 g). The amounts recorded in blackberries [27] and raspberries [28] ranging from 10.28 to 25.39 mg/100 g and 21 to 36 mg/100 g, respectively, were lower than data reported for pomegranate juice reaching 58 mg of vitamin C/100 g [29].…”
Section: Chemical Compositionmentioning
confidence: 69%
“…It is considered that many of the health benefits associated with berry fruits dietary intake are linked to their high polyphenols content. As a consequence, a growing number of scientific reports attempting to clearly address this link are now available [5,6]. A mixture of berry/wild fruits is used in winter time, to prepare various beverages considered as having both nutritional and therapeutic benefits.…”
Section: Introductionmentioning
confidence: 99%